2018
DOI: 10.1007/s00222-018-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the generating series of walks in the quarter plane

Abstract: In the present paper, we use difference Galois theory to study the nature of the generating series counting walks in the quarter plane. These series are trivariate formal power series Q(x, y, t) that count the number of discrete paths confined in the first quadrant of the plane with a fixed directions set. While the variables x and y are associated to the ending point of the path, the variable t encodes its length. In this paper, we prove that if Q(x, y, t) does not satisfy any algebraic differential relations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 33 publications
0
110
0
4
Order By: Relevance
“…We refer to [25,26] for a comprehensive overview of the background and early stages of this far-reaching project, and to [15,22] for some recent developments which are gateways to references. Finally, let us mention a remarkable recent development [49], which proves D-transcendence for many families of lattice walks. Let us single out just one of the many results in that paper:…”
Section: 2mentioning
confidence: 98%
“…We refer to [25,26] for a comprehensive overview of the background and early stages of this far-reaching project, and to [15,22] for some recent developments which are gateways to references. Finally, let us mention a remarkable recent development [49], which proves D-transcendence for many families of lattice walks. Let us single out just one of the many results in that paper:…”
Section: 2mentioning
confidence: 98%
“…7 (algebraic?) non-D-finite [34] non-D-finite [27,7,14] (non-D-finite?) Table 2: Algebraic nature of the conformal mapping w, the quadrant generating function Q(x, y) and the three-quarter plane counting function C(x, y)…”
Section: Modelmentioning
confidence: 99%
“…5]. Starting from (14) we can prove that c(X 0 (y))L −0 (X 0 (y)) + X 0 (y) d(y)D(y) − X 0 (y)y = 0 for y ∈ {y ∈ C : |X 0 (y)| < 1} ∩ D, and then c(X 0 (y)) n 0,j 0 c 0,−j−1 (n)X 0 (y) j t n + d(y)D(y) − y = 0 for y ∈ {y ∈ C : |X 0 (y)| < 1 and X 0 (y) = 0} ∩ D which can be continued in G L ∪ D. Being a power series, D(y) is analytic on D and on (G L ∪ D) \ D, D(y) may have the same singularities as X 0 and d(y), namely the branch cuts [y 1 , y 2 ] and [y 3 , y 4 ]. But none of these segments belong to (G L ∪ D) \ D (see Lemma 3).…”
Section: Proof Of Lemmamentioning
confidence: 99%
“…For these walks, by symmetry, the solutions (l, h, g) of (3.2) satisfy the relation h(x, t) = g(x, t) and have positive integer coefficients. In fact, it has been recently shown that the generating series corresponding to these 7 types of walks are among those that are x-hypertranscendental and yhypertranscendental [DHRS18]. That is, Q(x, 0, t) (resp.…”
Section: Figurementioning
confidence: 99%